Historic conversations on life with John F. Kennedy - Onassis, Jacqueline Kennedy, 1929-1994; Schlesinger, Arthur M., (Arthur Meier), 1917-2007; Beschloss, Michael R. (New York : Hyperion, 2011)
Presents the annotated transcription and original audio for the 1964 interviews with Jacqueline Kennedy on her experiences and impressions as the wife of John F. Kennedy, offering an intimate and detailed account of the man and his times.
Issued in slipcase.
Includes bibliographical references (p. 354-356) and index.
Keywords: Onassis, Jacqueline Kennedy, -- 1929-1994 -- Interviews; Kennedy, John F. -- 1917-1963; Onassis, Jacqueline Kennedy, -- 1929-1994 -- Interviews; Kennedy, John F. -- 1917-1963; Presidents' spouses -- United States -- Interviews; Presidents' spouses -- United States -- Interviews